Estudio de la adquisición de maquinarias industriales para el sector metalúrgico y su incidencia en las ventas - Gualotuña Caiza, Neiser Alfredo (2021)
This article referring to the study of the acquisition of industrial machinery for the metallurgical sector and its impact on sales, seeks that industrial machinery have state-of-the-art technology to make operations more productive with quality and multiple benefits, the general objective is to enable the use of foreign machinery for the production of stainless steel products for the gastronomic sector, among which is the optimization of times and resources for a better performance of companies in the city of Guayaquil.